Risk factors for carotid plaque progression after optimising the risk factor treatment: substudy results of the Atherosclerotic Plaque Characteristics Associated with a Progression Rate of the Plaque and a Risk of Stroke in Patients with the carotid Bifurcation Plaque Study (ANTIQUE). Issue 2 (1st December 2021) - Školoudík, David; Kešnerová, Petra; Hrbáč, Tomáš; Netuka, David; Vomáčka, Jaroslav; Langová, Kateřina; Herzig, Roman; Belšan, Tomáš
Abstract : Background and aim: Carotid plaque progression contributes to increasing stroke risk. The study aims to identify factors influencing carotid plaque thickness progression after changing the preventive treatment to the 'treating arteries instead of risk factors' strategy, that is, change in treatment depending on the progression of atherosclerosis. Methods: The study participants who completed sonographic controls over the course of 3 years were enrolled to the analysis. Duplex sonography of cervical arteries was performed in 6-month intervals with measurement of carotid plaque thickness. Plaque thickness measurement error (σ) was set as 3 SD. Only evidently stable and progressive plaques (defined as plaque thickness difference between initial and final measurements of ˂σ and >2σ, respectively) were included to analysis. Univariate and multivariate logistic regression analysis was performed to identify factors influencing plaque progression. Results: A total of 1391 patients (466 males, age 67.2±9.2 years) were enrolled in the study. Progressive plaque in at least one carotid artery was detected in 255 (18.3%) patients. Older age, male sex, greater plaque thickness, coronary heart disease, vascular surgery/stenting history and smoking were more frequently present in patients with progressive plaque (p˂0.05 in all cases). Multivariate logistic regression analysis identified only the plaque thickness (OR 1.850 for left side, 95% CI 1.398 to 2.449; and OR 1.376 for right side, 95% CI 1.070 to 1.770) as an independent factor influencing plaque progression. Conclusion: Carotid plaque thickness corresponding to stenosis severity is the only independent risk factor for plaque thickness progression after optimising the prevention treatment. Trial registration number: NCT02360137 .